Green Accounting, Environmental Performance: Mediating Role of Corporate Governance - Eni Suharti; Dhea Zatira; Sulhendri Sulhendri; Munzir Munzir; Sustari Alamsyah (Journal of Accounting and Finance Management, 2026)
The focus of this research is to investigate the mediating role GCG in the relationship between green accounting, environmental performance, and financial performance of chemical companies listed IDX period 2019 – 2023 with a sample of 10 companies, where green accounting and environmental performance variables become independent variables with corporate governance as an intervening variable and financial performance as independent variables. The analysis used in this study is panel data regression to test the hypothesis and mediation test through the Sobel test with the help of EViews software. The results of the study are: green accounting and environmental performance partially affect corporate governance, green accounting, environmental performance and corporate governance have a positive effect on financial performance. The implications of this study show that the company's attention to environmental aspects through green accounting practices and environmental performance improvement, supported by good corporate governance, is able to encourage improved financial performance.